La ciencia posneoclásica y la filosofía, y el problema del héroe literario - del personaje - Safronova, Liudmila (Cuadernos de Rusística Española, 2012)
The author is focused on the issue of a literary character as it is analyzed in the most influential currents of the contemporary theory of literature and philosophy of culture: structuralism and semiotics, narratologу, cognitology of literary criticism, the communication theory, deconstructivism, postmodernist and other poststructuralist theories.